GANGGUAN KECEMASAN SEBAGAI SUMBER INSPIRASI IDE DALAM PENCIPTAAN KARYA SENI LUKIS - Bayu Arisuta, I Gede; Tjokropramono, I Gede Yosef; Jodog, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2025)
This final report of this independent study/project raises the theme of anxiety disorders as a source of inspiration for the idea of creating a work of art. Anxiety disorders are a category of psychological disorders associated with feelings of anxiety and fear that occur excessively. Fear usually arises because of emotional or psychological feelings. Fear can also arise because of threats both physically and non-physically. The factors that underlie anxiety disorders are trauma, environment, and genetic factors. The problem faced is how to apply the concept, how to visualize the meaning contained in the work of art, what materials and media will be used in creating the work. The goal to be achieved in creating this work is to find out how anxiety disorders through creativity and imagination into the form of a work of art by combining certain techniques, styles, colors, and references to achieve the desired goal. From the theme above, there are 5 (five) works that can be realized with the titles: Claustrophobic, I Got PTSD, I Got GAD, Keep It Clean, and I Feel To. It can be concluded that anxiety disorders inspire the author in creating works of art and developing imaginative ideas and concepts, which will become valuable and meaningful works. With the creation of this work, it is hoped that it will be able to convey a moral message, as well as being an educational medium about anxiety disorders.